Women’s Agency in Korean Consumer Society in the Korean Drama Little Women - Maria Angela Runkat (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This article examines why the three sisters in Little Women Korean Drama strive to fulfill the demands of Korean consumerism and how they navigate the structure of Korean consumer society. Drawing upon Baudrillard’s consumer society theory and Giddens’ agency and structure theory, the study analyzes the reasons of the main characters—Oh In Joo, Oh In Kyung, and Oh In Hye—fulfilling the demands of Korean consumerism, driven by financial struggles, social marginalization, and lack of social power. It also explores the ways they navigate the structure of Korean consumer society by exercising their agency through their actions. The findings reveal that the power of agency produced by social pressure, represented by consumer society, shapes individuals in different ways. The study concludes that agency fosters resilience, determination, passion, allowing people to challenge social limitations and create the life they aspire to.